Oocyte polarized light microscopy, assay of specific follicular fluid metabolites, and gene expression in cumulus cells as different approaches to predict fertilization efficiency after ICSI - Alberto Revelli; Stefano Canosa; Loredana Bergandi; Oleksii A. Skorokhod; Valentina Biasoni; Andrea Carosso; Angela Bertagna; Milena Maule; Elisabetta Aldieri; Maria Diletta D'Eufemia; Francesca Evangelista; Nicola Colacurci; et al. (BMC, 2017)
Abstract Background The complex relationship between oocyte morphology, specific follicular fluid metabolites, gene expression in cumulus granulosa cells, and oocyte competence toward fertilization and embryo development still needs further clarification. Methods Forty-six oocytes retrieved from the largest pre-ovulatory follicle of patients undergoing intra-cytoplasmic sperm injection (ICSI) were considered assessing: (a) oocyte morphological characteristics at polarized light microscopy (PLM), (b) specific follicular fluid (FF) metabolites previously suggested to influence oocyte competence (AMH, markers of redox status and of cytotoxicity), (c) transcription of AMH and AMH type II receptor genes in cumulus cells. Data were analyzed using mono-parametric tests and multivariable logistic analysis in order to correlate morphological and biochemical data with fertilization. Results Comparing normally fertilized oocytes (n = 29, F group) with unfertilized (n = 17, nF group) we observed that: (a) the meiotic spindle area and major axis were significantly higher in nF group and in fertilized oocytes undergoing an early embryo development arrest; (b) AMH level in FF was comparable in F and nF groups; (c) the FF of nF group contained significantly higher levels of cytotoxicity (lactate dehydrogenase) and oxidative stress (Cu,Zn-superoxide dismutase, catalase, 4-hydroxynonenal-protein conjugates) markers; (d) cumulus cells of nF group showed significantly higher AMH receptor type II gene expression. Conclusions Taken together, these observations suggest that an excessive cytotoxicity level can alter AMH signal transduction within cumulus cells, in turn leading to partial inhibition of aromatase activity, altered cytoplasmic maturation and increased oxidative stress, factors able to impair oocyte fertilization competence and embryo growth.